Addressing child labour: reflections on the WTO's role. Issue 1 (16th March 2015) - Williams, Jessica
Abstract : Purpose: – This paper aims to analyse whether the World Trade Organisation (WTO) covered agreements ought to be interpreted in a manner that enables an importing country to restrict or prohibit import of goods manufactured using child labour. This question is pertinent, given the WTO-covered agreements do not explicitly mention child labour, yet there is increasing international concern for the phenomenon of child labour, evidenced through international human rights law and international labour law treaties and a push by some developed countries' WTO Members for inclusion of a "social clause" governing child labour under the covered agreements. Design/methodology/approach: – This paper examines the WTO-covered agreements, current trends in interpretation of the covered agreements by panels and the Appellate Body (AB) and scholarly debate regarding connecting trade with labour standards and human rights. Findings: – This paper argues: that although inclusion of a social clause in the covered agreements is unlikely, Article XX(a) GATT, Article XX(b) GATT and Article 2.1 TBT can in certain circumstances be interpreted as to allow such restrictions on the import of goods; that no clear academic argument logically precludes connecting trade with labour standards and human rights; and that to legitimate both the WTO and the international legal system as a whole, the covered agreements, as the basis of international trade law, ought to be interpreted in a manner consistent with international labour law and international human rights law. Originality/value: – This paper draws upon the recent AB decision in European Commission – Seal Products, examining the AB's interpretation of the Article XX(a) GATT "public morals" exception. This paper further seeks to provide a succinct overview of the argument surrounding WTO involvement in the issue of child labour.